Wolf–Hirschhorn syndrome: A case series from India. Issue 12 (10th September 2020) - Chaudhry, Chakshu; Kaur, Anit; Panigrahi, Inusha; Kaur, Anupriya
Abstract: Wolf–Hirschhorn syndrome (WHS) (OMIM#194190) is a contiguous gene syndrome with estimated prevalence being around 1 in 50, 000 births. The syndrome is caused by deletion of a critical region (Wolf–Hirschhorn Syndrome Critical region—WHSCR) on chromosome 4p16.3. Its core features are typical facial gestalt, growth retardation, intellectual disability, or developmental delay and seizures. We describe four patients, each highlighting a different aspect of this syndrome. One patient was detected by karyotype where a large deletion was identified. Three other children were diagnosed after targeted multiplex ligation‐dependent probe amplification (MLPA) where heterozygous deletion of the probes on chromosome 4p16.3 were identified. One of these children additionally had heterozygous duplication of the probe for chromosome band 5p13.3. Less than half of the patients can be identified by conventional cytogenetics and molecular cytogenetic testing should be offered for diagnosis. Karyotyping of the parents should always be offered in a child with WHS.